Herring Gulls Larus argentatus in Common Eider Somateria mollissima feeding flocks a discerning kleptoparasite - Waltho, Chris M (Wildfowl, 2013)
In Scotland, feeding flocks of Common Eider Somateria mollissima are regularly attended by Herring Gulls Larus argentatus which attack and steal food from the eiders. This study describes the prey brought to the surface by the eiders, their prey handling behaviour, subsequent attacks by gulls, and the outcome of such attacks. The majority of the prey was Blue Mussel Mytilus edulis (80%) but Green Urchin Psammechinus miliaris, Shore Crab Carcinus maenas and Common Starfish Asterias rubens were also taken. Attack frequency was not related to the occurrence of each type of prey in the eiders’ diet, except that gulls were only observed attacking eiders for nonmussel prey. Attacks were most frequent (79%), and most successful (i.e. losses to gulls were highest), against eiders with starfish (73% of prey lost) and crabs (50% of prey lost). In contrast, losses of urchins (4%) and mussels (0%) were low. Despite starfish accounting for < 4% of Common Eider prey, gulls won sufficient (73%) to make kleptoparasitism a common feature of feeding flocks of eiders in this study area. These results indicate that Herring Gulls are highly selective in their attacks on Common Eider, and in the prey that are targeted.